(untitled) (Issues in Social and Environmental Accounting (ISEA), 2013)
The Clean Development Mechanism (CDM), established under the Kyoto Protocol, is one of the market-based mechanisms developed to assist industrialized countries mitigate greenhouse gas (GHG) emissions, achieve emission reduction targets, and at the same time promote sus tainable development in developing countries. The CDM, which provides flexibility and cost effectiveness in meeting GHG emission reduction targets, has captured interest globally. CDM implementation is expected to generate benefits, give developing countries a sense of owner ship, and share the global load in tackling global warming and climate change. However, CDM implementation faces several complications. The successful participation of developing coun tries in emission reduction projects presents ongoing challenges, which inhibit their drive to wards sustainable development goals. Through a comprehensive review of the literature and theoretical analysis, several factors have been identified as significant to successful CDM im plementation in Malaysia. These success factors, which include regulation and a legal frame work, competitive advantage, green supply chain, ethical values, financial benefits, and tech nology transfer, are presented and the importance of each factor is discussed.